Unraveling the role of H3K4 trimethylation and lncRNA HOTAIR in SATB1 and DUSP4-dependent survival of virulent Mycobacterium tuberculosis in macrophages. (January 2020) - Subuddhi, Arijita; Kumar, Manish; Majumder, Debayan; Sarkar, Arijita; Ghosh, Zhumur; Vasudevan, Madavan; Kundu, Manikuntala; Basu, Joyoti
Abstract: The modification of chromatin influences host transcriptional programs during bacterial infection, at times skewing the balance in favor of pathogen survival. To test the role of chromatin modifications during Mycobacterium tuberculosis infection, we analysed genome-wide deposition of H3K4me3 marks in macrophages infected with either avirulent M. tuberculosis H37Ra or virulent H37Rv, by chromatin immunoprecipitation, followed by sequencing. We validated differences in association of H3K4me3 at the loci of special AT-rich sequence binding protein 1 ( SATB1 ) and dual specificity MAP kinase phosphatase 4 ( DUSP4 ) between H37Rv and H37Ra-infected macrophages, and demonstrated their role in regulating bacterial survival in macrophages as well as the expression of chemokines. SATB1 repressed gp91 phox (an NADPH oxidase subunit) thereby regulating reactive oxygen species (ROS) generation during infection. Long non-coding RNA HOX transcript antisense RNA (HOTAIR) was upregulated in H37Ra-, but downregulated in H37Rv-infected macrophages. HOTAIR overexpression correlated with deposition of repressive H3K27me3 marks around the TSSs of DUSP4 and SATB1, suggesting that its downregulation favors the transcription of SATB1 and DUSP4 . In summary, we have delineated histone modification- and lncRNA-dependent mechanisms regulating gene expression patterns facilitating survival of virulent M. tuberculosis . Our observations raise the possibility of harnessing histone-modifying enzymes to develop host-directed therapies for tuberculosis.